Analisis Faktor Model Pengukuran Persepsi Keamanan Nasional Generasi Muda Youth Percieved National Security Factor Analysis Measurement Model - Amadeo, Alfa Duta; Wardoyo, Broto (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2022)
Theorists have argued many perspectives and multidimensionality of national security, therefore identifying essential factors of them becomes an important issue in the measurement model. Based on Stephan’s theories on intergroup threats theory and Jacob’s about the top of five models of national security,it was constructed a questionnaire to measure the perceived national security of the younger generation (APKN). This research aims to measure the level of reliability, and validity and identify the main factors of APKN. The sample was 333 out of 373 students and employees, characterized by age 16-30 years old selected randomly The result showed APKN questionnaire which consists of 35 items had a level of Cronbach Alpha reliability of 0.703, 21 items were valid and there were three main factors found: security dimension, social-economic dimension, and barrier dimension.